2008
DOI: 10.1002/adem.200700331
|View full text |Cite
|
Sign up to set email alerts
|

Conductive Heat Transfer in Metallic/Ceramic Open‐Cell Foams

Abstract: During the last decade, solid foams which are characterized by a relatively high porosity (> 80 %), have known a strong development. Indeed, they allow to envisage a substantial improvement of the performance of standard materials in numerous technological fields. Notably, metallic and ceramic foams exhibit thermal, mechanical and exchange properties, which make them very interesting in lots of applications requiring multifunctionality. To illustrate this, we can cite a non-exhaustive list of functions for whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…1 and 2 although its density is more important. This global increase of k c with the density is consistent with theoretical conclusions of previous studies [7] which underlined the substantial influence of the volume fraction of highly conductive solid phase on the conductive heat transfer. The surprising results evocated for sample No.…”
Section: Presentation and Discussion On The Experimental Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…1 and 2 although its density is more important. This global increase of k c with the density is consistent with theoretical conclusions of previous studies [7] which underlined the substantial influence of the volume fraction of highly conductive solid phase on the conductive heat transfer. The surprising results evocated for sample No.…”
Section: Presentation and Discussion On The Experimental Resultssupporting
confidence: 92%
“…3 might be explained by a noticeable difference in the porous structure between this foam and the other samples. Indeed, Coquard et al [7] have already shown that the shape of the struts forming the cellular materials could have a noticeable influence on the magnitude of conductive heat transfer.…”
Section: Presentation and Discussion On The Experimental Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The fluid phase effective thermal conductivity is given by k f,eff = /k f . Of the various correlations that were considered for k s,eff [46,[54][55][56], Coquard et al [57] and Kamuito [58] establish that the analytical expression obtained by Schuetz and Glicksman [56] for polyurethane foams is the most applicable, as it adequately (within 30% of experimental measurements) represents thermal conductivities of open cellular structures. The lower limit for k s,eff in Eq.…”
Section: Heat Exchanger Modelmentioning
confidence: 99%